Stimulasi Pertumbuhan Planlet Anggrek (Dendrobium Sp) Dengan Pemberian ZPT Atonik dan Root Most Pada Masa Aklimatisasi : Stimulation of Orchid Plantlet Growth (Dendrobium Sp) By Giving Atonic ZPT and Root Most During Acclimatization - Faradilla; Yuanita; F. Silvi Dwi Mentari (HUTAN TROPIKA, 2021)
Acclimatization is an indicator of success in tissue culture techniques. Without acclimatization, the plant will remain in the bottle and have no value. Acclimatization is the transfer of plantlets from the microenvironment (in the bottle) to the external environment (soil, sand). The dendrobium orchid is a very popular type of orchid traded, but its growth rate is slow. Atonic ZPT and root most are ZPT which contain a lot of auxin. The purpose of the study was to compare the types and concentrations of PGR that were appropriate for the acclimatization of Dendrobium orchids in order to increase plant growth. The study was conducted experimentally using a non-factorial Completely Randomized Design (CRD) consisting of 7 treatment levels. The levels of treatment were as follows: control, atonic PGR 2 ml/l, atonic PGR 3 ml/l, atonic PGR 4 ml/l, PGR root most 2 ml/l, PGR root most 3 ml/l, and PGR root most 4 ml/l. Each treatment level was repeated 9 times. The results showed that giving atonic PGR and root most had a significant effect on the variables of plant height increase, leaf number increase and primary root length increase and had no significant effect on the increase in stem diameter. The best results were shown by giving atonic PGR at 3 ml/l in all variables except for the increase in primary root length, which was indicated by the treatment with PGR root at most 3 ml/l.